Factors that influence health-related quality of life in newly diagnosed patients with multiple myeloma aged ≥ 65 years treated with melphalan, prednisone and lenalidomide followed by lenalidomide maintenance: Results of a randomized trial - Dimopoulos, M.A.; Palumbo, A.; Hajek, R.; Kropff, M.; Petrucci, M.T.; Lewis, P.; Millar, S.; Zhang, J.; Mei, J.; Delforge, M. (Leukemia and Lymphoma, 2014)
In the MM-015 trial, melphalan-prednisone-lenalidomide followed by lenalidomide maintenance (MPR-R) significantly prolonged progression-free survival versus melphalan-prednisone (MP) in newly diagnosed patients with multiple myeloma aged ≥ 65 years. Health-related quality of life (HRQoL), a secondary endpoint of MM-015, was also improved with MPR-R. This sub-analysis evaluated the impact of individual predictive factors on HRQoL. Patients completed HRQoL questionnaires at baseline, every third cycle and at progressive disease (PD)/treatment discontinuation. In a mixed-effects model female gender, advanced age and PD negatively affected HRQoL while better treatment responses showed positive effects. Compared to PD, HRQoL during MPR-R treatment was statistically significantly better in two of six preselected domains both of which were also clinically meaningful. HRQoL scores at end of treatment were all either improved or not statistically significantly different versus baseline. In conclusion, continuous treatment with MPR-R, which delays PD, appears to be associated with clinically meaningful improvements in HRQoL. © 2014 Informa UK, Ltd.
Keywords: Health-related quality of life (HRQoL); Lenalidomide; Minimal important difference (MID); multiple myeloma; QLQ-C30; QLQ-MY20